TOWARD A EUROPEAN TORT LAW OF DATA PROTECTION: THE CASE LAW OF THE COURT OF JUSTICE OF THE EUROPEAN UNION AND ITS IMPACT ON NATIONAL TORT LAWS - Bubalo, Lana; Novović, Miloš (Pravni zapisi, 2025)
The paper examines the provisions governing non-material damage resulting from violations of the right to personal data protection under the General Data Protection Regulation (GDPR), as well as their interpretation in the case law of the Court of Justice of the European Union (CJEU). Particular attention is devoted to judgments in which the Court develops autonomous, yet insufficiently precise, legal concepts, thereby creating legal uncertainty and complicating the application of relevant provisions at the national level. Although the CJEU has entrusted national courts with the assessment of damages, the paper emphasizes that in practice it is impossible to fully separate the conditions for awarding damages from the process of determining the amount of compensation.
Keywords: GDPR; Tort Liability; Non-Material Damage; Court of Justice of the European Union